Public Schools in Hard Times: The Great Depression and Recent Years - Axelrod, Paul (Labour / Le Travail, 1986)
This article reviews the book, "Public Schools in Hard Times: The Great Depression and Recent Years," by David Tyack, Robert Lowe & Elisabeth Hansot.